Evaluation of Study of Research Methodology Courses (Implementation of Ralph W. Tyler's Goal-Oriented Model Program Evaluation) - Fauzobihi, Fauzobihi; Rustomo, Rustomo; Annishia, Fristi Bellia; Ramadhina, Retno (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The Pertiwi School of Economics is one of the private campuses in the city of Bekasi and has classes in various areas has two majors in S1 Management and S1 Accounting. The author in this case will conduct research on Evaluation of Research Methodology Course Learning using the Goal Oriented Model Ralph W. Tyler. The focus of this evaluation research is the achievement of learning programs that are considered important which can be seen from: How are the problems in the input evaluation aspect, which include, the quality of lecturers, the presence of lecturers, study plans that have never been reviewed, facilities and infrastructure. This approach uses program objectives as criteria to determine the success or achievement of a program. Evaluators try to measure the extent to which the goals have been achieved and conduct analysis and observations of national and international articles to support this research. The object of observation in this model is the goal of the program that has been set. For research methodology courses, almost all lecturers have carried out evaluations at the end of the teaching and learning process in the classroom. However, the results obtained are sometimes unsatisfactory. Sometimes the results achieved are substandard or below average. Tyler's goals-oriented program evaluation is designed to describe successful program goals. Evaluation is also meaningful for drawing conclusions which includes three main things in the process, namely formulating questions, collecting data, and presenting or displaying information. Contributive evaluation has advantages in the decision-making process in a goals-oriented evaluation approach, namely its straightforwardness. The goals-oriented evaluation approach is fast to follow, understand, apply and easy to agree on and master when researched